Children in the Aftermath of the Great Recession - Carsten Andersen; Mikkel Aagaard Houmark; Helena Skyt Nielsen; Michael Svarer (Institute of Labor Economics (IZA), 2022)
In this paper we study effects of mass layoffs on parents and their children in the aftermath of the Great Recession using staggered difference-in-differences (DiD). We exploit quasi-experimental variation in announcements of mass layoffs in Danish firms in 2008-2019. We document that parents exposed to a mass layoff during and immediately after the Great Recession are negatively affected 6 years after the event; more so and for a longer period of time for parents at high risk of long term unemployment. Perhaps surprisingly, we find no overall significant negative effects of parental mass layoffs on children; neither academic achievement, absenteeism nor well-being are affected. We even find some positive effects for the children of parents who were more adversely affected by the layoff, consistent with an increase in parental time investment following unemployment. This last finding would not have appeared using a traditional two-way fixed effects approach, which appears to be biased towards zero in our setting.
Keywords: I20; J63; 330; wellbeing; school outcomes; unemployment; mass layoff; academic achievement